2014
DOI: 10.1128/jvi.00943-14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of the Airborne Transmissibility of H9N2 Avian Influenza A Viruses in Chickens

Abstract: H9N2 avian influenza virus has been prevalent in poultry in many parts of the world since the 1990s and occasionally crosses the host barrier, transmitting to mammals, including humans. In recent years, these viruses have contributed genes to H5N1 and H7N9 influenza viruses, threatening public health. To explore the molecular mechanism for the airborne transmission of H9N2 virus, we compared two genetically close strains isolated from chickens in 2001, A/chicken/Shanghai/7/2001(SH7) and A/chicken/Shanghai/14/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 61 publications
2
44
0
Order By: Relevance
“…These results showed that the chicken flocks infected by H9N2 AIV form and transmit viral aerosols. In addition, the results support previously published papers where exposure to H9N2 AIV aerosols is considered an important route of airborne transmission within chicken flocks [25][26][27].…”
Section: Discussionsupporting
confidence: 81%
“…These results showed that the chicken flocks infected by H9N2 AIV form and transmit viral aerosols. In addition, the results support previously published papers where exposure to H9N2 AIV aerosols is considered an important route of airborne transmission within chicken flocks [25][26][27].…”
Section: Discussionsupporting
confidence: 81%
“…Zhong et al further identified that the amino acids 363K in the HA gene and 672L in the PA gene contribute to the airborne transmissibility of the H9N2 AIVs in chickens and they also confirmed the importance of these two residues by evaluating the airborne transmission ability of 18 casually chosen natural H9N2 viruses carrying these two residues in chickens [160] . Notably, the proportion of strains with both PA 672L and HA 363K increased in 1998, which coincided with the epidemicity of H9N2 viruses in China [39] .…”
Section: Transmission Of the H9n2 Aivsmentioning
confidence: 88%
“…The H9N2 virus can be transmitted by airborne droplets to chickens which may account partially for their fast spread among flocks and to individual birds [66,159,160] . Zhang et al have shown that most of the H9N2 viruses isolated before 2000 fail to be transmitted efficiently to aerosol contact groups of chickens [66] .…”
Section: Transmission Of the H9n2 Aivsmentioning
confidence: 99%
“…Aerosol transmission is one of the most important pathways for influenza virus to spread among poultry, from poultry to mammals, and among mammals [911]. In recent years, human infection with many subtypes of AIVs has been reported, including H5N1, H5N6, H7N9, H10N8, H6N1, and H9N2 AIVs, and field epidemiological investigation showed some patients had no history of direct contact with any live poultry before illness onset [3, 12, 13].…”
Section: Introductionmentioning
confidence: 99%